KSHV and the pathogenesis of Kaposi sarcoma: listening to human biology and medicine - Ganem, Don (American Society for Clinical Investigation, 2010)
The linkage of Kaposi sarcoma (KS) to infection by a novel human herpesvirus (Kaposi sarcoma–associated herpesvirus [KSHV]) is one of the great successes of contemporary biomedical research and was achieved by using advanced genomic technologies in a manner informed by a nuanced understanding of epidemiology and clinical investigation. Ongoing efforts to understand the molecular mechanisms by which KSHV infection predisposes to KS continue to be powerfully influenced by insights emanating from the clinic. Here, recent developments in KS pathogenesis are reviewed, with particular emphasis on clinical, pathologic, and molecular observations that highlight the many differences between this process and tumorigenesis by other oncogenic viruses.